Fourth Industrial Revolution and Future of Work in Asia - Falendra Kumar Sudan (Global Economics Science, 2021)
The Fourth Industrial Revolution (4IR) has significant implications on the future of work and skills required in the gig economy. In the recent past, a large supply of young workers had led to rapid economic transformation in many Asian countries through well-suited education systems to create skills needed for employment. However, the old model of education and production will no longer sustain rapid growth in the decades ahead due to the rapidly changing demand for skills. Against the above backdrop, the paper has analyzed Asian experiences in technological transition, skills mismatches and labour market outcomes in the context of existing technical and vocational education and training (TVET) systems. What are the challenges and opportunities of the 4IR for skill development through TVET in Asia? The paper has suggested a model for 4IR compatible skill development for the future of the work and draws the implications for the future. 4IR induced massive job losses calls for adequate skills development or retraining of displaced workforce and new entrants in foundational skills to enable them to tap the opportunities of new technologies. This requires robust TVET systems to equip workers with new skills for emerging jobs, which can be possible by increasing the quality of program structure to meet the needs of labour market. The technical training should be integrated into with the secondary education through education reforms to impart skills to thrive in the knowledge economy. The system of quality apprenticeships should be evolved with the active collaboration of potential employers in the curriculum development of TVET programs.